Early therapy with neuraminidase inhibitors for influenza A (H1N1) pdm 2009 infection. Issue 6 (12th August 2013) - Yamamoto, Takehisa; Ihashi, Mai; Mizoguchi, Yoshimi; Kaneno, Hiroshi; Yamamoto, Katsusuke; Inoue, Yutaka; Kase, Tetsuo; Okabe, Nobuhiko; Shimotsuji, Tsunesuke
Abstract Background Neuraminidase inhibitors have been reported to decrease mortality in patients infected with influenza A (H1N1) pdm 2009 (H1N1 pdm09), but it is not clear whether they are effective againstH1N1pdm09 in apparently healthy children. Methods The effect of early treatment with neuraminidase inhibitors on 70 otherwise healthy children with possible H1N1 pdm09 (pH1N1pdm09) infection was investigated. The children were simultaneously treated with a neuraminidase inhibitor (oseltamivir or zanamivir) and maoto, a Japanese traditional herbal medicine, which had been reported to be effective against seasonal influenza. Clinical severity was assessed using patient history, namely the worst values for clinical vital signs and laboratory data on admission. After refining these parameters with univariate, decision tree and multiple regression analysis, mean covariance structure equation analysis was used to investigate the association of estimated clinical severity to the selected parameters. Results Total path analysis using a Bayesian method indicated that the estimated clinical severity of pH1N1pdm09 was positively associated with maximum body temperature, pulse rate, respiration rate, duration necessary for defervescence, admission duration and log urinary β2‐microglobulin/creatinine level, and negatively associated with age and the presence and duration of treatment with the neuraminidase inhibitor in the outpatient clinic. Conclusions This study provides the first clinical evidence that early treatment with neuraminidase inhibitors in outpatient clinic decreased the estimated clinical severity of pH1N1pdm09 in apparently otherwise healthy pediatric inpatients.